Economic assessment of non-sinusoidal energy in distorted distribution systems. Issue 1 (6th March 2019) - Kumar, Narinder; Kumar, Ashwani
Abstract : Purpose: The purpose of this paper is to analyze annual energy expenditure in the presence of non-linear load and substation voltage harmonics in distribution systems. Economic assessment of non-sinusoidal energy is a challenging task that involves complex computations of harmonic load powers and harmonic line losses. Design/methodology/approach: The paper evaluates fundamental and non-sinusoidal components of electrical energy by applying backward/forward sweep technique in distorted distribution systems. This work involves harmonic power computations at the substation by including harmonic losses occurring in various lines of the distribution system. Findings: The paper found that annual energy expenditure significantly depends upon the non-linear load, supply voltage harmonics and type of tariff structure considered in the distribution system. Impact of individual harmonic orders on the energy billing is also assessed. Originality/value: The paper concludes that considering harmonic distortions in the distribution system analysis would help electricity regulators formulate adequate pricing structures, which would further generate appropriate economic signals for electricity utility and the consumers.